Tourism & tourist’s attitude: an overview / Ainna Syifaa Abu Khari, Ts Dr Nor Hanisah Mohd Hashim and Prof Dr Azlizam Aziz - Abu Khari, Ainna Syifaa; Mohd Hashim, Ts Dr Nor Hanisah; Aziz, Prof Dr Azlizam (UiTM Cawangan Negeri Sembilan, 2022)
Authorities often establish tourism related divisions or tourist agencies to assist aims in the sectors of tourism expansion and improvement. Tourist offices strengthen public-private partnerships in worldwide tourism marketing. Additionally, they have the potential to play a key central role. Tourism has always been a rising sector. Tourism has been a thriving international industry since the immediate post-war period, and especially after 1950. The world's industrialised countries are the primary source of visitors.